Synchronous breast and colon cancer in a young female: a single stage surgery - Abushwemeh, Mohammed Ayed; Jabeen, Nusrat; Al Qaseer, Asma; Isa, Mohamed; Al Rayes, Amal; Al Marzooq, Raed (International Surgery Journal, 2021)
Synchronous breast and colon cancers are rare, particularly in the absence of family history. Synchronous tumors should always be kept in mind during the staging workup for the primary malignancy. There are no definitive guidelines for the management of synchronous tumors, thus the involvement of tumour board multidisciplinary team is essential. We present a case of a young female patient who was diagnosed with synchronous breast and colon cancer. A handful of synchronous breast and colon cancer cases have been reported and operated at intervals, but up to our knowledge this is the first case operated simultaneously in a single stage surgery.